Adaptive mating memory: Attractiveness and contextual effect on the remembering and misremembering of potential mates’ faces - TAY, Peter Kay Chai (Institutional Knowledge at Singapore Management University, 2017)
Research on adaptive memory demonstrates that words and objects are remembered better if they are evaluated in relation to their survival or reproductive fitness value. Using the error management theory as a framework to elucidate memory biases emerging from adaptive costs and benefits, the present research examined if memory is enhanced for faces of potential mates (i.e., opposite sex individuals) in an ancestral context when the facial attractiveness and the observer’s short-term mating motive were also considered (i.e., Adaptive mating memory). In two studies, participant read scenarios depicting survival threats, mating, or modern environment, and were told to rate a set of faces based on these scenarios. After the rating task, they were given a surprise memory test. In both studies, participants were generally more accurate for unattractive faces than attractive faces, and they tended to falsely recognized attractive opposite sex faces more frequently compared to unattractive opposite sex faces. In addition, women falsely recognized attractive female faces more frequently than other types of faces, consistent with the female intrasexual competition hypothesis. Across both studies, women demonstrated more accurate memory for faces compared to men, and context did not influence memory for faces, regardless of attractiveness, target sex, and participant sex. Findings from the present research suggest that adaptive memory for potential mates’ faces emerges at the interface of costs and benefits associated with facial cues (i.e., face sex, and attractiveness), and is invariant of the context the faces are situated in.